Keterangan Waktu Non-Predikatif Bahasa Jepang - Roni Roni; Didik Nurhadi (Jurnal Lingua Idea, 2019)
This study focuses on non-predicate adverbs of time in Japanese. From the data analysis it can be concluded as follows. Adverbs of time can be divided into two, namely adverbs of time in quality and adverbs of time in quantity. Adverbs of time in quality consists of at least four groups. State (1) day, week, date, month and year, (2) now, tomorrow, day after tomorrow, yesterday, today, this morning, and so on, (3) hours, (4) a certain time. Adverbs of time in quality can at least be divided into two groups. State (1) nuanced amount, (2) nuanced distance. Adverbs on time is generally indicated by postposition ni (on). There are three types of usage ni, namely mandatory, not required, and optional. Lastly, the use of the postposition wa to signify that the phrase of adverbs is the topic of conversation in the sentence.